The Role of Digital Forensics as Qarinah Muasirah in Proving Cyber Offences Under Malaysian Islamic Evidence Law - Tuan Ibrahim, Tuan Muhammad Faris Hamzi; Nasrul Hisyam Nor Muhamad; Mohamad Aniq Aiman Alias; Ahmad Syukran Baharuddin (AL-ISTINBATH : Jurnal Hukum Islam, 2026)
The rise of cybercrime cases such as online gambling (al-maysir) and zina through digital platforms poses an unprecedented challenge to the classical evidentiary structure in Islamic criminal law. Traditional evidentiary methods (wasail al-ithbat) such as iqrar and shahadah are increasingly difficult to apply, especially in digital crime cases without physical interaction or direct witnesses. As a response to this evidentiary gap, digital forensics, which is based on validated scientific procedures, offers a reliable approach through the process of identifying, preserving and analyzing digital evidence. This study aims to examine how this digital forensic method can be recognized and integrated within the framework of Islamic criminal law, specifically as a valid form of qarinah (circumstantial evidence) according to the principles of syariah evidence. This study uses a qualitative approach through document analysis that includes primary and secondary sources. Data were examined through qualitative content analysis using inductive approach. In addition, analogical reasoning was employed to bridge digital forensic evidence with classical concepts of qarinah derived from the Qur'an and hadith. This integrated approach allows for a critical synthesis between Islamic evidentiary principles and modern digital forensic methodologies. This study finds that digital evidence through forensic procedures is capable of providing strong evidentiary value within the framework of Islamic evidence law. These evidentiary forms conceptually correspond to the classical Islamic notions of qarinah through al-'alamat and al-amarat, which function as recognised indicators of criminal conduct. The findings also reveal that the logic underlying Locard’s Exchange Principle, which affirms that every action leaves a trace is not foreign to Islamic legal reasoning. In Malaysian legal system, The Syariah Court Evidence Act 1997 [Act 561] and Syariah Court Practice Directions issued by the Department of Syariah Judiciary Malaysia (JKSM) provide a normative basis for admitting digital evidence as means of proof. Relatively, the integration of digital forensics into the framework of Islamic evidence law upholds the dynamic capacity of the Syariah to uphold the maqasid Syariah. However, the study identifies notable procedural and institutional limitations where religious enforcement officers lack digital forensic expertise and existing directives such as the 2007 Standing Instruction and Practice Direction No. 4 of 2020 remain general, outdated and lack of technical or verification standards for digital evidence.